Influencer Credibility, Parasocial Relationships, and Product Involvement in Purchase Intentions - Tripopsakul, Suchart; Hoonsopon, Danupol (Emerging Science Journal, 2025)
The increasing influence of social media influencers (SMIs) on consumer purchase intentions has become a crucial topic in marketing research, particularly in understanding the mechanisms that drive this effect. This study examines how SMI credibility—defined by trustworthiness, expertise, and attractiveness—affects consumer purchase intentions through the mediating role of parasocial relationships (PSRs) and the moderating role of product involvement. A survey of 205 Thai social media users was conducted, and data were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that SMI credibility positively impacts purchase intentions and strengthens PSRs, which partially mediate this relationship. Moreover, the moderating role of product involvement uncovers a conditional mediation effect: PSRs have a stronger influence on purchase intentions for low-involvement products, where emotional appeals are more effective than rational evaluations. In contrast, for high-involvement products, consumers prioritize cognitive processing and influencer expertise, weakening the impact of PSRs. This research enhances influencer marketing literature by incorporating emotional and cognitive pathways within a mediated-moderated framework. Practically, it highlights the importance of aligning influencer strategies with product involvement, recommending emotionally engaging influencers for low-involvement products and credibility-driven influencers for high-involvement products to maximize marketing effectiveness.